Digital Learning of English Beyond Classroom: EFL Learners’ Perception and Teaching Activities - Arif Nugroho; Arief Eko Priyo Atmojo (JEELS (Journal of English Education and Linguistics Studies), 2020)
The shift of language learning from face-to-face classroom interaction to online learning beyond classroom amidst global pandemic of Covid-19 has changed how teachers and students deal with teaching and learning activities. To address the issue, the present study sheds some light on 71 EFL learners’ perception toward digital learning of English beyond classroom and a range of English learning activities in social distancing measures. Drawing on the data from a web-based survey and Focus Group Discussion, the results indicated that the students positively perceived the use of digital technology as a means of language learning amidst the global pandemic. It was also revealed that digital learning of English beyond classroom could potentially be conducted by means of available social networking sites such as Youtube, WhatsApp, Instagram, Google classroom, and Facebook. Some activities using digital learning of English beyond classroom are clearly highlighted. The results of this study contribute to the realm of language teaching in offering some insights for designing beyond classroom activities by augmenting the accessible social networking sites.